A nine‐channel transmit/receive array for spine imaging at 10.5 T: Introduction to a nonuniform dielectric substrate antenna. Issue 4 (26th November 2021) - Sadeghi‐Tarakameh, Alireza; Jungst, Steve; Lanagan, Mike; DelaBarre, Lance; Wu, Xiaoping; Adriany, Gregor; Metzger, Gregory J.; Van de Moortele, Pierre‐Francois; Ugurbil, Kamil; Atalar, Ergin; Eryaman, Yigitcan
Abstract : Purpose: The purpose of this study is to introduce a new antenna element with improved transmit performance, named the nonuniform dielectric substrate (NODES) antenna, for building transmit arrays at ultrahigh‐field. Methods: We optimized a dipole antenna at 10.5 Tesla by maximizing the B 1 + ‐SAR efficiency in a phantom for a human spine target. The optimization parameters included permittivity variation in the substrate, substrate thickness, antenna length, and conductor geometry. We conducted electromagnetic simulations as well as phantom experiments to compare the transmit/receive performance of the proposed NODES antenna design with existing coil elements from the literature. Results: Single NODES element showed up to 18% and 30% higher B 1 + ‐SAR efficiency than the fractionated dipole and loop elements, respectively. The new element is substantially shorter than a commonly used dipole, which enables z ‐stacked array formation; it is additionally capable of providing a relatively uniform current distribution along its conductors. The nine‐channel transmit/receive NODES array achieved 7.5% higher B 1 + homogeneity than a loop array with the same number of elements. Excitation with the NODES array resulted in 33% lower peak 10g‐averaged SAR and required 34% lower input power than the loop array for the target anatomy of the spine. Conclusion: In this study, we introduced a new RF coil element: the NODES antenna. NODES antenna outperformed the widely used loop and dipole elements and may provide improved transmit/receive performance for future ultrahigh field MRI applications.